Carbohydrate hydrogel beverage provides no additional cycling performance benefit versus carbohydrate alone - Baur, D. A.; Toney, H. R.; Saunders, M. J.; Baur, K. G.; Luden, N. D.; Womack, C. J. (European Journal of Applied Physiology, 2019)
Purpose: This study examined the effects of a novel maltodextrin-fructose hydrogel supplement (MF-H) on cycling performance and gastrointestinal distress symptoms. Methods: Nine endurance-trained male cyclists (age = 26.1 ± 6.6, mass = 80.9 ± 10.4 kg, VO2max = 55.5 ± 3.6 mL/kg/min) completed three experimental trials consisting of a 98-min varied-intensity cycling protocol followed by a performance test of ten consecutive sprint intervals. In a cross-over design, subjects consumed 250 mL of a treatment beverage every 15 min of cycling. Treatments consisted of 78 g/hr of either (a) MF-H, (b) isocaloric maltodextrin-fructose (ratio-matched 2:1; MF), and (c) isocaloric maltodextrin only (MD). Results: There were no differences in average sprint power between treatments (MF-H, 284 ± 51 W; MF, 281 ± 46 W; and MD, 277 ± 48 W), or power output for any individual sprint. Subjective ratings of gastrointestinal distress symptoms (nausea, fullness, and abdominal cramping) increased significantly over time during the cycling trials, but few individuals exceeded moderate levels in any trial with no systematic differences in gastrointestinal discomfort symptoms observed between treatments. Conclusions: In conclusion, ingestion of a maltodextrin/fructose hydrogel beverage during high-intensity cycling does not improve gastrointestinal comfort or performance compared to MF or MD beverages.